Changes in diagnosis and treatment of congenital adrenal hyperplasia - tertiary center experience - Milenković, Jana; Milenković, Tatjana; Sedlecki, Katarina; Ilić, Predrag; Martić, Jelena; Mitrović, Katarina; Todorović, Slađana; Marjanović, Marko; Tončev, Jovana; Panić-Zarić, Sanja; Pešić, Danilo; Vuković, Rade (Medical Research, 2023)
Introduction: Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive diseases caused by deficiency of enzymes responsible for the steroidogenesis. The most common cause of CAH is 21-hydroxylase deficiency, which presents in three forms: the classic form with salt loss, the classic virilizing and the non-classical form. Aim of this paper was to analyze changes in the diagnosis and treatment of children with CAH during previous 15 years.Material and methods: This retrospective cohort study includes patients who were diagnosed with CAH in the period from 2007- 2021 in the endocrinology department of the Mother and Child Health Care Institute of Serbia "Dr Vukan Cupic". Subjects were divided into a group whose diagnosis was made in period from 2007-2014 and another group of those whose diagnosis was made from 2015-2021. Statistical analysis using Chi-square and Mann Whitney U test was conducted using software “IBM SPSS ver. 22”, and p values